Enhancing Graduate Employability Through Soft-Skill Practice In University Malaysia Terengganu - Tajib, Kamal; Yusoff, Nur Athirah (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research Aim: This study explores the relationship between leadership, communication, interpersonal, and ethics on the employability of graduates from Universiti Malaysia Terengganu (UMT). Method: This research applied a quantitative method with 260 respondents from UMT alumni. Data were collected through closed-ended questionnaires and analyzed using the Statistical Package for Social Science (SPSS). Multiple regression analysis was conducted to test the hypotheses. Research Finding: The results indicate that communication skills and ethics significantly affect the employability of UMT graduates, whereas leadership and interpersonal skills show no significant relationship. Ethics emerged as the most influential variable, with a beta coefficient of 0.826. Theoretical Contribution/Originality: This study highlights the importance of soft skills, particularly ethics and communication, in enhancing the employability of UMT graduates. It supports the literature that technical skills alone are insufficient to determine employability; they must be combined with soft skills. Practitioner/Policy Implication: The findings suggest educational policy implications, where universities should focus on developing students' soft skills, particularly ethics and communication, to improve graduate employability. Leadership and interpersonal skills development programs could also be enhanced. Research Limitation: This study is limited to UMT alumni and utilizes only quantitative data. Future research should involve other universities and consider qualitative approaches to gain deeper insights into other factors influencing employability.